Reliability of fair value presentation to investors in a depressed economy: case of Zimbabwe - Phiri, Shelton (Midlands State University, 2017)
The research focused on the reliability of fair value presentation to investors in a depressed economy being a case of Zimbabwe. The research was inspired by an increase in the number of cases where investors lost their investments in companies that presented their financial statements using unreliable fair values. Both foreign and domestic investors are losing millions of dollars to companies which are using fair values to window dress their financial statements hiding the true economic values of the companies. Such practices are only getting exposed in the face of liquidation or major ownership transfers but at such point it will be too late for investors to recover their investments. Literature relating to the study was also analysed so as to strengthen the base of the study. Descriptive and explanatory research approaches with a population census size of 35 respondents was used in gathering primary and secondary data. The research also used questionnaires and interviews as data collection instruments. Tables, graphs and charts were used in presenting and analysing the collected data. The research proved that fair values were relevant and reliable in financial decisions made by investors and they should be extensively used in financial reporting.